Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

Ad

A cat reaches the approximate human age of 15 during its first year, then 24 at age 2. Each year thereafter, it ages approximately 4 "cat years" for every calendar year. So a 5-year-old feline would be approximately 36 in cat years. Your kitty is very old, if measured by these figures. I found this info on the Internet. Google "how can I tell how old my cat is in human years" and you'll get a lot of information. Good luck.

Mar 10, 2017 | Cats

This is due to the AGE of your account, not your age.

It was ceased because you did not use in the time, in other words the account aged due to lack of use.

It was ceased because you did not use in the time, in other words the account aged due to lack of use.

Feb 04, 2015 | Yahoo Computers & Internet

Let m be Marian's age, d Diana's age and c Carlos age.

I hope I helped :)

- sum of ages is 17: m+d+c=17
- two years from now Marian will be twice as old as Diana: m+2=2*(d+2) so m+2=2d+4 so 2d=m-2 or d=(m-2)/2=m/2-1
- Carlos will be half as old as Marian 4 years from now: c+4=1/2(m+4) or c+4=m/2+2 or c=m/2-2
- now: m+d+c=m+m/2-1+m/2-2=17
- 2m=17+3=20
- m=20/2=10 years
- d=m/2-1=5-1=4 years
- c=m/2-2=5-2=3 years

I hope I helped :)

Sep 18, 2011 | Office Equipment & Supplies

Todd is 4 years old.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

Correction: **Bob is thrice as old as Peter.**

Let b be the current age of Bob, and p the current age of Peter.**Now, b=3p**

Six years earlier the relations was:**b-6=4*(p-6)=4p-24.**

Take the 6 to the right side leaving b=4p-18

Remember that now b=3p. Use it in the equation above

b=(3p)=4p-18, This becomes 3p=4p-18 or 0=p-18, and**p=18**

**Peter is 18 years old, and Bob is 3*18=54 years old.**

Verification: 6 years ago Peter was 12 years old and Bob 48 years old. 48/12=4.

Let b be the current age of Bob, and p the current age of Peter.

Six years earlier the relations was:

Take the 6 to the right side leaving b=4p-18

Remember that now b=3p. Use it in the equation above

b=(3p)=4p-18, This becomes 3p=4p-18 or 0=p-18, and

Verification: 6 years ago Peter was 12 years old and Bob 48 years old. 48/12=4.

Aug 10, 2011 | Texas Instruments TI-84 Plus Calculator

So the father is 3 times as old as his daughter.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Jul 19, 2011 | Computers & Internet

Within 11 years, the age of Peter will be half the square of the age he was 13 years ago. Calculate the current age of Peter.

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Sep 22, 2010 | Computers & Internet

Hi,

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Mar 17, 2010 | Disney Watches

Edwin is 14. Ruel is 7.

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

Dec 11, 2008 | Computers & Internet

Oct 22, 2017 | Book Computers & Internet

Oct 22, 2017 | Quantum Computers & Internet

14 people viewed this question

Usually answered in minutes!

×